Social support, parenting style and mental health of children and adolescents - Midori Sakuramoto, Sandra; Elisabeth Squassoni, Carolina; Simões Matsukura, Thelma (O Mundo da Saúde, 2014)
Literature suggests that parenting practices and social support received by parents are factors that influence mental health of children and adolescents; practices may predict the development of pro-social and antisocial behavior of children; regarding social assistance, there is a relationship between satisfaction and positive indicators of development. The purpose of the study was to identify correlations between social support from parents, family parental practices and mental health of children. Fifty one pairs took part in the present study, composed by father or mother and their children with ages ranging from 11 and 13 years old. The instruments used to collect data were: Social Support Questionnaire, Parental Style Inventory, Strengths and Difficulties Questionnaire and an identification questionnaire. Data analysis was performed using Pearson’s correlation study. The outcomes indicate that the greater the social support and the more positive the parental style, the less risky it is for children to present any mental health problem. The challenge for future research and development of actions among families relates to the development of interventions that can reach parents to enlighten them about the importance of practical daily care and attention to children, even when there are adverse living conditions.